2008
DOI: 10.2196/jmir.957
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Internet-Based Technology for Supporting Self-Care: Problems Encountered by Patients and Caregivers When Using Self-Care Applications

Abstract: BackgroundPrior studies have shown that many patients are interested in Internet-based technology that enables them to control their own care. As a result, innovative eHealth services are evolving rapidly, including self-assessment tools and secure patient-caregiver email communication. It is interesting to explore how these technologies can be used for supporting self-care.Objective The aim of this study was to determine user-centered criteria for successful application of Internet-based technology used in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
113
0
10

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(133 citation statements)
references
References 21 publications
10
113
0
10
Order By: Relevance
“…[32,38,43] Within the literature, it is indicated that the principle users should be given key priority, which in the current study were family members. As such, family members should continue to play an active role in the continuous process improvement and the post-implementation evaluation of the EPHR.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…[32,38,43] Within the literature, it is indicated that the principle users should be given key priority, which in the current study were family members. As such, family members should continue to play an active role in the continuous process improvement and the post-implementation evaluation of the EPHR.…”
Section: Discussionmentioning
confidence: 95%
“…[21,27,28] Additional EPHR concerns were highlighted that were linked to the sensitive nature of personal healthcare information, which have been identified in several other studies. [13,23,[42][43][44][45][46][47][48][49][50] One third of family members in the current study reported concerns associated with confidentiality and security when considering the implementation of an EPHR. For example, concerns about security of personal information were found at the top of a list of concerns linked with an EPHR in a study conducted by the Markle Foundation (2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With advances in information technology, the importance of terminology also extends to interactions with tools for medical decision-making (Nijland et al, 2008). Decision aids, like the strategy for off-site rapid triage, a web-based decision aid designed in response to the 2009 H1N1 influenza pandemic, aim to provide better informed decision-making during times of medical crisis (Kellermann et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Editor. Los problemas en salud pública tienen un impacto inmediato en medios de comunicación, en los últimos años Internet ocupa un lugar importante en ellos por la rapidez y facilidad con que se transmite la información siendo consultado especialmente por poblaciones de grandes ciudades, tanto a través de páginas especializadas como de buscadores generales (1,2) .Estas búsquedas quedan registradas en Internet y se han utilizado con éxito para predecir el comportamiento de un brote epidémico, mostrando un potencial valor y costo efectividad como herramienta de vigilancia para identificar tempranamente brotes epidémicos, incluso antes de que este sea anunciado oficialmente por instituciones de salud; la vigilancia basada en las tendencias de búsquedas de términos específicos, ingresados por usuarios de Internet a motores de búsqueda como Google, abren además un nuevo campo de investigación denominado epidemiología de la información o infodemiología; sin embargo, esta novedosa forma de pesquisa de epidemias no ha sido diseñada para reemplazar a las redes de vigilancia tradicional (3)(4)(5) .Con el objetivo de evaluar si existe una correlación entre las búsquedas en Google realizadas por usuarios de Internet en Perú para el término "dengue" y los casos notificados de un reciente brote en la costa norte del Perú, se elaboró un modelo con el volumen relativo de ambos, donde se incluye, además, el número de artículos periodísticos peruanos relacionados con el dengue, disponibles en Internet, buscando determinar si el incremento de búsquedas en Google es proporcional al incremento en el número de artículos periodísticos en Internet.El número total de casos de dengue notificados por las direcciones regionales de salud de Piura, Lambayeque, La Libertad y Tumbes, se obtuvo de los boletines semanales de la Dirección General de Epidemiología (DGE), disponibles en su página web (www.dge.gob.pe/ boletin2010.php).La frecuencia de búsquedas realizadas por usuarios de Internet en Perú usando la palabra "dengue" se obtuvo de la aplicación para estadísticas de búsquedas de Google denominada "Google Insight" (www.google.com/insights/ search/#), del cual se exportó los registros históricos de búsquedas durante las primeras 26 semanas del año 2010, estos datos se expresan como volumen relativo, es decir datos normalizados en una escala del 0 al 100, donde este último valor representa el máximo de búsquedas realizadas en el periodo de búsqueda, similar estrategia fue usada para analizar la curva de casos notificados de dengue. Los resultados se encuentran en la siguiente dirección Web: http://bit.ly/e2p5Q6…”
unclassified